Screen Recording Video in Virtual Learning During Covid-19 Pandemic: Students' Perspective - Lisa Suhayati; Haryati Haryati (Universitas Hamzanwadi, 2021)
The application of digital tools has been used in educational institution including universities to strengthen the material delivery. They can be beneficial tools in COVID-19 pandemic condition as teachers' assistance. Due to these issues, this study was conducted to determine students' perspective on the implementation of screen recording video in virtual learning activities during Covid-19 pandemic. This study involved 50 participants of the sixth semester students of English department of Universitas Pamulang. To obtain the data, the writers distributed a questionnaire consisting 10 questions and interviewed 4 questions to the students related to the implementation of virtual learning in COVID-19 pandemic situation. The data analysis reveals that the students have top four positive responses of screen video recording in virtual learning: enhancing the quality of learning, helping students learn more effectively, enhancing students’ learning experience, students-teachers' engagement, and flexible time and place. They also find that teachers' assistance and guidance are still absolutely needed however beneficial screen recording video is.